(untitled) (Mugda Medical College Journal, 2024)
Malaria is transmitted by the Plasmodium parasite, and often reported in Bangladesh in patients with a history recent travel to an endemic zone. Malaria is endemic in 13 of 64 districts in Bangladesh. About 14 million people are at risk. Prompt diagnosis and treatment is essential in preventing mortality. Severe malaria represents a medical emergency because it may rapidly progress to complications and death without prompt and appropriate treatment and almost exclusively caused by Plasmodium falciparum. The incidence of imported malaria is increasing and the case fatality rate remains high despite progress in antimalarial treatment. Clinical deterioration usually appears 3-7 days after onset of fever. Complications involve the nervous, respiratory, renal, and/or hematopoietic systems. Metabolic acidosis due to renal failure is a common systemic complication. We are reporting here a case of severe malaria in a 30-year-old man who presented with fever, myalgia, and reduced urination for two days. Mugda Med Coll J. 2022; 5(1): 46-49